2017
DOI: 10.22159/ijcpr.2017v9i4.20959
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Nutritional Profile and Antioxidant Potential of Different Dioscorea Sp With Plectranthus Rotundifolius

Abstract: Objective: Protection from oxidative damage to the tissues is provided by natural or synthetic antioxidants. Because of the multiple mechanisms of actions and presence of various phytochemicals, plant-based antioxidants are preferred. Dioscorea is well known as a traditional edible tuber. The present study was undertaken to explore and highlights the nutritional benefits and to evaluate the in vitro antioxidant and free radical scavenging capacity of ethanolic extract of three different underutilised Dioscorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Erythrina edulis is a native species that, despite its high protein and good amino acid profile, is being underestimated and underexploited. Like other indigenous crops, E. edulis is in danger of being replaced by other cultivated species and of suffering continuous genetic erosion, putting at risk a food resource of local populations [22].…”
Section: Resultsmentioning
confidence: 99%
“…Erythrina edulis is a native species that, despite its high protein and good amino acid profile, is being underestimated and underexploited. Like other indigenous crops, E. edulis is in danger of being replaced by other cultivated species and of suffering continuous genetic erosion, putting at risk a food resource of local populations [22].…”
Section: Resultsmentioning
confidence: 99%
“…These crops, which have not been previously categorized as major crops and are mainly confined to smallholder farming areas, are nutrient-dense, climate-resilient, and locally adaptable (Li and Siddique, 2020;Mudau et al, 2022). The erosion of these crops can hinder the nutritional status and food security of the poor, and their greater use can augment nutrition and fight hidden hunger (Dansi et al, 2012;Ojuederie et al, 2015;Joy and Siddhuraju, 2017). It is crucial that we recognize the hidden potential of these crops and harness them to achieve a more sustainable future.This editorial spotlight promising research showcasing the hidden potential of NUCs and exploring their utilization through modern advancements.…”
mentioning
confidence: 99%
“…Other species within the genus of Plectranthus are also used as a medicinal plant for various disease categories such as digestive disease, skin, respiratory, infections or fever, urinary system, and pain treatment (Lukhoba et al, 2006). A study on physicochemical analysis of black potato showed that the tuber has several essential minerals and various active substances such as tannins and flavonoids, which generate antioxidant and anti-inflammatory activities (Joy and Sidhuraju, 2017). In Indonesia, black potato is less popular compared to sweet potato and cassava.…”
mentioning
confidence: 99%